Effects of anesthetic drugs on otoacoustic emissions: Experimental study (Annals of Medical Research, 2021)
Aim: Otoacoustic emission measurements are generally performed under sedation for children and experimental animals. In the literature it is stated that due to systemic effects of medications used with the aim of sedation, there are variations in cochlear perfusion and as a result, otoacoustic emission (OAE) measurements are affected. Our study aims to investigate this interaction.Material and Methods: The study was completed using 15 healthy adult Wistar Albino rats. The rats were divided into three groups based on anesthetic agent used; group midazolam (M), group ketamine (K) and group dexmedetomidine (D). After OAE measurements were performed in Groups M and D, noradrenalin was administered, OAE measurements were repeated and these were defined as group MN and Group DN. During the study, the hemodynamic data and OAE measurement results were recorded. Results were assessed for statistical significance.Results: The mean arterial pressure in Group M and Group D was 66±16 mmHg, while in Group K, Group DN and Group MN it was 134±16. The mean HR in Group M and Group D was 196±20 beats/min, while in Group K, Group DN and Group MN it was 170±40 beats/min. In Group M and D, there was a correlation with mean arterial pressure only at 2 and 4 kHz, while in the noradrenalin group there was a direct correlation identified for mean arterial pressure only at 6 kHz.Discussion: Though it is frequently emphasized in the literature that in addition to direct pharmacological effects of anesthetic agents, they may affect OAE results due to hemodynamic changes, in our study we conclude there is no significant interaction in clinical terms.Keywords: Sedation; otoacoustic emission measurements; cochlear hypoperfusion.
Keywords: Sedation; otoacoustic emission measurements; cochlear hypoperfusion.